Influence of sex on quality aspects of horse meat - De Marzo, Davide; Nicastro, Francesco; Facciolongo, Anna Maria; Nicastro, Annarita (Progress in Nutrition, 2015)
The aim of this research is to study the influence of sex on quality indices of horse meat in Italian market. Fourteen male and female horse (TPR x genetic type Abruzzese) have been bred. All foals were slaughtered between 24 and 26 months of age. After slaughter on Longissimus dorsi muscle samples were determined pH, color, shear forces and cooking losses. The most important results were found on the evolution of pH during meat storage and on color immediately after slaughter and over time. Interesting data also show the degree of tenderness and cooking losses by demonstrating a different meat water holding capacity of the two sexes.